2021
DOI: 10.1101/2021.02.13.431107
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Influence of warming temperatures on coregonine embryogenesis within and among species

Abstract: The greatest response of lakes to climate change has been the increase in water temperatures on a global scale. The responses of many lake fishes to warming water temperatures are projected to be inadequate to counter the speed and magnitude of climate change, leaving some species vulnerable to decline and extinction. We experimentally evaluated the responses of embryos from a group of cold, stenothermic fishes (Salmonidae Coregoninae), within conspecifics across lake systems, between congeners within the same… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 134 publications
(212 reference statements)
0
14
0
Order By: Relevance
“…The rapidity at which winter environments are changing has revealed our ‘blind spot’ for winter biology (Ozersky et al, 2021). The results presented here and elsewhere (Karjalainen et al, 2016, 2015; Stewart et al, 2021a, 2021b) focus on how coregonine reproduction may be impacted by a warming climate and suggest that while we have much to learn, the effects of warming winters will vary among populations and with the magnitude of warming. These results highlight the importance of integrating natural habitat preferences into stock propagation programs to ensure offspring are set up for success upon reintroduction.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…The rapidity at which winter environments are changing has revealed our ‘blind spot’ for winter biology (Ozersky et al, 2021). The results presented here and elsewhere (Karjalainen et al, 2016, 2015; Stewart et al, 2021a, 2021b) focus on how coregonine reproduction may be impacted by a warming climate and suggest that while we have much to learn, the effects of warming winters will vary among populations and with the magnitude of warming. These results highlight the importance of integrating natural habitat preferences into stock propagation programs to ensure offspring are set up for success upon reintroduction.…”
Section: Discussionmentioning
confidence: 74%
“…The match-mismatch hypothesis postulates that larval survival is dependent on a temporal and spatial match between larval feeding capabilities, such as swimming ability and prey acquisition, and prey availability (Cushing, 1990). Warmer incubation temperatures lead to earlier hatch dates and altered morphological developments, such as smaller lengths and larger yolk sacs, that reduce larval feeding efficiency (Darowski et al, 1988), compared to colder incubated embryos (Karjalainen et al, 2015; Stewart et al, 2021a). The selective pressures from elevated temperatures on embryonic and larval coregonine development and survival may lead to adaptation, but the thermal trigger for the response and the mechanism of the response are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison, Lake Superior cisco showed a trade-off between LAH and YSV. A negative relationship between LAH and YSV is common in fish temperature incubation studies (Blaxter, 1991; Karjalainen et al, 2015; Stewart et al, 2021), but the relationship is usually accompanied by a change in incubation period as basal metabolic demand consumes yolk as a function of the length of incubation. We found that light influenced incubation periods similarly among light treatments; therefore, the trade-off between LAH and YSV in Lake Superior cisco suggests decreased yolk conversion efficiency to somatic tissue occurred as light intensity increased.…”
Section: Discussionmentioning
confidence: 99%
“…The design is fully described in Stewart et al (2021). Briefly, gametes were stripped from 12 females and 16 males from each lake and artificially fertilized to create 48 families from each lake.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation